Response surface optimization of the process conditions for anti-diabetic compounds from Cucumis Sativus - Jamal, Parveen; Ahmad Barkat, Anumsima; Amid, Azura (Academic Journals, 2011)
Presently, there is a growing interest in herbal remedies due to the side effects associated with the use of insulin and oral hypoglycaemic agents for diabetic patient. Therefore an investigation is required in a bionetwork rich and industrially-developed country like Malaysia to use alternative approaches to treat diabetics, such as plant based medicine. In this study, Cucumis sativus was examined on the basis of their use in traditional medicines throughout Southeast Asia, to develop an understanding of the distribution and to give an assessment of the diversity present in the selected plant. β-glucosidase inhibitory activity reached the highest value of 96.81% at the optimum conditions of temperature, 25.66°C; incubation time, 22.30 h ; agitation speed, 125 rpm and volume of solvent, 15.6 ml. High Performance Liquid Chromatography (HPLC) analysis identified five compounds, out of which two were identified as p-coumaric acid and syringic acid while the other three were unknown. These two phenolic acids are already known to have anti-diabetic properties from previous study. This potential plant with β-glucosidase inhibitory activity can be a hope for millions for treatment of diabetes and will also help in reducing the dependence on synthetic drugs in the future.